2015
DOI: 10.4103/0974-9233.159762
|View full text |Cite
|
Sign up to set email alerts
|

Determinants of visual outcomes in femtosecond laser assisted cataract surgery and phacoemulsification: A nested case control study

Abstract: Purpose:We present the visual outcomes 6 weeks following Femtosecond laser assisted cataract surgery (FLACS) and conventional phacoemulsification cataract extraction (CE) cataract surgeries in 2013.Materials and Methods:This was a review of health record type of study. Eyes operated by FLACS and an equal number of conventional phacoemulsification (CE) on the same day by same surgeon were included in the study. Demographics, preoperative status, operative details and the best-corrected visual acuity (BCVA) at 6… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

0
3
0
2

Year Published

2016
2016
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 7 publications
(5 citation statements)
references
References 25 publications
0
3
0
2
Order By: Relevance
“… 9 , 10 However, it remains unclear whether or not performing these steps with the laser translates to improvements in refractive outcomes over the current standard cataract surgery procedure. 4 , 11 …”
Section: Introductionmentioning
confidence: 99%
“… 9 , 10 However, it remains unclear whether or not performing these steps with the laser translates to improvements in refractive outcomes over the current standard cataract surgery procedure. 4 , 11 …”
Section: Introductionmentioning
confidence: 99%
“…2, 3: n=89; критерий Манна-Уитни; среднее; отрезки: среднее ±0,95 доверительный интервал. ственных различий [9,10]. Авторы говорят о высокой стоимости фемтолазерных систем и необходимости долгосрочных исследований по данному вопросу [9].…”
Section: рис 1 нкоз до на момент выписки и через 4 мес после фэк иunclassified
“…ственных различий [9,10]. Авторы говорят о высокой стоимости фемтолазерных систем и необходимости долгосрочных исследований по данному вопросу [9]. Не отмечая статистической разницы в визуальных и рефракционных результатах между технологиями при проведении метаанализа опубликованных данных с 2007 по 2016 г. на 14 567 глазах, авторы подчеркивают увеличение концентрации простагландинов после ФЛАЭК, но отмечают снижение эффективного времени факоэмульсификации во время операции [10].…”
Section: рис 1 нкоз до на момент выписки и через 4 мес после фэк иunclassified
“…To date, many studies have attempted to compare the outcome and complications of FLACS and CPCS. Some studies have shown better visual acuity recovery and lower endothelial cell loss after FLACS when compared with CPCS [ 5 , 6 ], whereas others have detected no significant difference between the two technologies [ 7 , 8 ]. We herein performed this systematic study in order to evaluate the treatment efficacy and complications of FLACS and CPCS, including visual recovery, corneal cell integrity, and functionality in an aim to provide guidance for clinical practice.…”
Section: Introductionmentioning
confidence: 99%